2019
DOI: 10.1021/acsnano.9b08061
|View full text |Cite
|
Sign up to set email alerts
|

Transformation Cycle of Magnetosomes in Human Stem Cells: From Degradation to Biosynthesis of Magnetic Nanoparticles Anew

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(71 citation statements)
references
References 55 publications
5
65
1
Order By: Relevance
“…One of them is to shield the magnetic core with an inert gold shell [112,113], and another one is to protect the core with a polymer coating [114]. Alternatively, another strategy could be to seize the capacity that some human cells must biosynthesize magnetic nanoparticles anew from the iron delivered by the degradation of synthetic nanoparticles, thus providing the cells with biogenic non-degradable nanoparticles and long term magnetism [115,116].…”
Section: Long-term Stability and Biodistribution Of Nano-heaters In Hmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them is to shield the magnetic core with an inert gold shell [112,113], and another one is to protect the core with a polymer coating [114]. Alternatively, another strategy could be to seize the capacity that some human cells must biosynthesize magnetic nanoparticles anew from the iron delivered by the degradation of synthetic nanoparticles, thus providing the cells with biogenic non-degradable nanoparticles and long term magnetism [115,116].…”
Section: Long-term Stability and Biodistribution Of Nano-heaters In Hmentioning
confidence: 99%
“…the core with a polymer coating [114]. Alternatively, another strategy could be to seize the capacity that some human cells must biosynthesize magnetic nanoparticles anew from the iron delivered by the degradation of synthetic nanoparticles, thus providing the cells with biogenic non-degradable nanoparticles and long term magnetism [115,116]. The spheroids are formed from 200,000 stem cells, which spontaneously regroup into a cohesive spherical aggregate that can be kept in culture over a month without experiencing any cell mortality or tissue necrosis.…”
Section: Long-term Stability and Biodistribution Of Nano-heaters In Hmentioning
confidence: 99%
“… 100 This highlights the benefit of the latter as a more predictive and representative biological model, particularly when quantitatively determining critical doses of administered materials, and the dynamics of material degradation in cells, as recently reported for biosynthesized magnetic iron nanoparticles. 102 …”
Section: Go Sheets Biodegrade In the Marginal Zone Macrophages Over Nmentioning
confidence: 99%
“…Using a similar system, Curcio et al studied the intracellular biodegradation of magnetosomes, a magnetite-based particle biosynthesized by Magnetospirillum magneticum . The authors found that by measuring cellular sample magnetization, human stem cells gradually degraded the magnetosome material into ferrihydrite within their lysosomal/endosomal compartment over 21 days [ 137 ]. As a consequence, photothermal conversion of stem-cell spheroids was lowered over time.…”
Section: Iron Oxide Nanoparticle Biodegradationmentioning
confidence: 99%
“…As a consequence, photothermal conversion of stem-cell spheroids was lowered over time. Curiously, Curcio et al also found that when magnetosome-loaded stem cells are cultured in 2-D, magnetization decreased by the third day of culture but recovered after 21 days, suggesting a de novo biosynthesis of intracellular magnetic nanoparticles, most likely out of the magnetosome degradation-derived iron pool [ 137 ]. Electron-microscopic evidence of IONP presence in cellular degradative compartments after internalization and changes in magnetization have thus established that IONPs are likely degraded intracellularly in lysosomal/acidic compartments and that this results in a loss of physical properties in the nanomaterial over time.…”
Section: Iron Oxide Nanoparticle Biodegradationmentioning
confidence: 99%